Improving the Wellbeing of Ikot Ene During the COVID-19 Lockdown: The Role of Justice, Development and Peace/Caritas Advocates (JDPCA) - Emmanuel M. Bekomsom; James A. Ogar; Abayomi I. Akintola; Emmanuella Dike; Tangban Egbe; Francis E. Ibioro; Adeolu Ayodele (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The study's objective is to examine the relationship between Justice, Development and Peace/Caritas Advocates (JDPCA) activities and the Wellbeing of Ikot Ene people during COVID-19 Lockdown. Specifically, the study examines the relationship between JDPCA’s provision of palliatives, healthcare programmes, and the Wellbeing of Ikot Ene people during COVID-19 Lockdown. Two research questions and null hypotheses were raised for the study. Literature was reviewed according to the variables of the study. The survey research design was adopted in collecting data from 176 samples from a population of 725 beneficiaries of the JDPCA programme from Ikot Ene in Akpabuyo Local government Area of Cross River state. The instrument of data collection was the question. Data collected from the field was analyzed using descriptive and inferential statistics. Result revealed a correlation between JDPCA’s provision of palliatives; healthcare programmes had a significant impact on the Wellbeing of the people of Ikot Ene. During COVID-19 Lockdown. Based on the study's findings, the study recommends a need for the Justice, Development and Peace/Caritas Advocates (JDPCA) to improve their coverage area and the number of beneficiaries for their future programmes.